Lean six sigma for the office - Martin, James William (Boca Raton, Florida : CRC Press, 2009)
The first section of this book is divided into three chapters. These include strategy alignment, project identification, and a discussion of several important operational elements that are characteristic of a Lean system. Strategy alignment implies that Kaizen events will be link to higher-level organization goals and objectives.
Align improvement opportunities -- Plan and conduct the Kaizen event -- Implementing solutions
Includes index.
Keywords: TOTAL QUALITY MANAGEMENT